INTEGRATION OF ISLAMIC EDUCATION AND SCIENCE IN THE PERSPECTIVE OF 21ST CENTURY LEARNING: A CRITICAL LITERATURE REVIEW - Maya Agustina; Fasya Fasella; Indah Sumaiyulisa; Nadiaton Hikmah (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2026)
This study aims to conduct a critical and comprehensive literature review regarding the integration model of Islamic Education and Science within the framework of 21st-century education. The method used is a critical literature review with a qualitative descriptive approach to scientific articles published between 2015 and 2025, obtained from Google Scholar, Garuda, DOAJ, as well as journals indexed in SINTA and reputable international journals. The analysis was carried out through identifying the integration paradigm, learning models, epistemological dimensions, and their implications for science literacy and character formation. The results indicate that the integration of Islam and science has evolved from an additive approach to a transformative integrative paradigm that emphasizes harmony between revelation and scientific rationality. Epistemologically, the integration can be mapped within the approaches of bayani, burhani, and 'irfani. Pedagogically, models such as Discovery Learning have proven effective in enhancing science literacy while supporting value reflection. However, the implementation of integration still faces obstacles such as low teacher competence, limited resources for integrative learning, and insufficient institutional support. This study emphasizes that the integration of Islam and science is a transformative project that requires epistemological reconstruction, pedagogical innovation, capacity building for educators, and systematic curriculum reform.